ARCHEOLOGICAL INVESTIGATION AT THE KHUDUTEPE MULTILAYERED SETTLEMENT OF THE MUGAN STEPPE IN 2021: BRIEF REPORT - Agalarzade, Anar Mirsamid; Nasirova, Lala Sahbal; Gusejnova, Matanat Muhammad (History, Archeology and Ethnography of the Caucasus, 2023)
The article discusses the results of archaeological exploration carried out at the multilayered settlement of Khudutepe, located in the Mugan steppe in the southeast of the Republic of Azerbaijan. The site was discovered in the 1990s by an archaeologist F. Makhmudov and preliminary dated to the Chalcolithic era. However, archaeological excavations have not been carried out here. Due to long-term economic activity on this territory, the site was gradually destroyed. Numerous archaeological finds discovered as a result of these destructions (pottery, weapons, jewelry, numismatic material, etc.) were handed over by the local population to the regional museum of local history. As a result of the work carried out, a settlement was found in the southern and southwestern parts of the hill, and a necropolis of the early Iron Age was located in the northern and northeastern parts. In 2021, the expedition of the Institute of Archeology, Ethnography and Anthropology of ANAS at the Khudutepe settlement carried out archaeological excavations, both of the necropolis and the settlement itself. During the study of the necropolis, three earthen burials were examined. The materials of the Khudutepe settlement obtained during the excavations testify to its multilayered nature and the intensive nature of the settlement of this area in different historical periods. Exploratory excavations at this site revealed cultural layers of the Late Chalcolithic, Early Bronze Age, Late Bronze Age – Early Iron Age and the medieval period. Favorable natural and climatic conditions contributed to the development here in the indicated historical periods of an integrated agricultural and cattle breeding economy, the formation of a local culture of the ancient population of the Mugan steppe. The northern and northeastern side of the hill is an Iron Age necropolis, and the southern and southwestern part is a residential area. During the investigations of 2021, major archaeological excavations were started both in the residential area and in the necropolis of Khudutepe, and a large number of material culture samples were discovered. At the same time, three earthen graves were discovered during excavations in the necropolis part of the monument. The archaeological excavations conducted in Khudutepe, the richness of the cultural layer proves that there was an intensive and continuous life here. The main reason for the existence of the monument, which includes all historical stages from the Chalcolithic period to the late Middle Ages, is the mild and favorable natural climate of this place. The presence of ancient river valleys with abundant water resources for sedentary agriculture and vast pastures created the foundation for the ancient population of Mughan steppe to create a rich culture here.